HLA-DRB1 alleles associated with polymyalgia rheumatica in northern Italy: correlation with disease severity. Issue 5 (1st May 1999) - Salvarani, Carlo; Boiardi, Luigi; Mantovani, Vilma; Ranzi, Andrea; Cantini, Fabrizio; Olivieri, Ignazio; Bragliani, Michela; Collina, Elisa; Macchioni, PierLuigi
Abstract : OBJECTIVE: To examine the association of HLA-DRB1 alleles with polymyalgia rheumatica (PMR) in a Mediterranean country and to explore the role of HLA-DRB1 genes in determining disease severity. METHODS: A five year prospective follow up study of 92 consecutive PMR patients diagnosed by the secondary referral centre of rheumatology of Reggio Emilia, Italy was conducted. HLA-DRB1 alleles were determined in the 92 patients, in 29 DR4 positive rheumatoid arthritis (RA) patients, and in 148 controls from the same geographical area by polymerase chain reaction amplification and oligonucleotide hybridisation. RESULTS: No significant differences were observed in the frequencies of HLA-DRB1 types and in the expression of HLA-DRB 70–74 shared motif between PMR and controls. The frequency of the patients with double dose of epitope was low and not significantly different in PMR and in controls. No significant differences in the distribution of HLA-DR4 subtypes were observed between DR4+ PMR, DR+ RA, and DR4+ controls. Results of the univariate analysis indicated that an erythrocyte sedimentation rate (ESR) at diagnosis > 72 mm 1st h, the presence of HLA-DR1, DR10, rheumatoid epitope, and the type of rheumatoid epitope were significant risk factors associated with relapse/recurrence. Cox proportional hazards modelling identified two variables that independently increased the risk of relapse/recurrence: ESR at diagnosis > 72 mm 1st h (RR=1.5) and type 2 (encoded by a non-DR4 allele) rheumatoid epitope (RR=2.7). CONCLUSION: These data from a Mediterranean country showed no association of rheumatoid epitope with PMR in northern Italian patients. A high ESR at diagnosis and the presence of rheumatoid epitope encoded by a non-DR4 allele are independent valuable markers of disease severity.